Boosting productivity in Kazakhstan with Mcro-Level Tools analysis and policy lessons - Iootty, Mariana; Bizhan, Asset; Correa, Paulo 1968- (The World Bank, 2022)
Like many other countries, Kazakhstan's economic growth has slowed since the 2007-09 global financial crisis. Although the slowdown reflected weaknesses in expanding labor and capital, the most striking reduction has been in productivity growth. In more recent years, total factor productivity growth has started to bounce back, albeit at a modest pace, possibly driven by the recovery in commodity prices. Although slower expansion in productivity has been a global phenomenon, Kazakhstan's subdued productivity performance for a decade reflects more structural problems. Against this backdrop, Boosting Productivity in Kazakhstan with Micro-Level Tools: Analysis and Policy Lessons examines barriers and policy gaps that hinder productivity growth in Kazakhstan. The detailed analysis is uniquely based on first-time access to administrative firm-level data; the data for the period of 2009-18 covered 70,000 business establishments annually, corresponding to total employment of 1.6 million people. The unprecedented access to firm-level data deepened the understanding of the microeconomic dynamics and drivers of aggregate productivity growth and enabled identification of a wide-ranging set of policy recommendations to boost aggregate productivity growth
Keywords: Decomposition Analysis; Factor Allocation; Firm Capabilities; Government Interventions; Manufacturing; Micro, Small and Medium Enterprises; MSME; Productivity Drivers